A new genus of the tribe Blondeliini (Diptera: Tachinidae: Exoristinae) from the Oriental Region with morphological and molecular evidence - Huang, Yu-Zen; Tachi, Takuji (Zootaxa, 2024)
In this study a new genus of the tribe Blondeliini, Shimamyia, is established. In this genus, Shimamyia exigua comb. nov., S. orientalis comb. nov., S. taiwanensis sp. nov., and S. vietnamensis sp. nov. are described and the key to species is provided. Shimamyia exigua and S. orientalis were initially identified as members of Medinodexia Townsend but were thought to belong to an undescribed genus based on external morphology and male and female postabdomens. The present study provides comprehensive descriptions of the four species. The phylogenetic tree reconstructed from 27 blondeliine species (including two from Shimamyia) and 6 outgroup using 16S, 28S, white, and CAD genes is also provided to discuss the placement of Shimamyia. Morphological and molecular evidence support the differentiation of Shimamyia from Medinodexia while confirming its inclusion in Blondeliini. Additionally, the modified female postabdomens of the new genus and other Blondeliini members are briefly discussed.